The antibiotic effects of apple cider vinegar on candida albicans and candida tropicalis. - Katu, Gregory Takudzwa (Midlands State University, 2019)
Candida species are the most common cause of fungal infections in humans. Candida species produce infections that range from non life-threatening mucocutaneous illnesses to invasive processes that may involve virtually any organ and this broad range of infections. Candida albicans coexists with a highly diverse human bacterial microbiota. Candida tropicalis is a common pathogen in neutropenic hosts in whom it may spread through the bloodstream to peripheral organs. Candida tropicalis has been identified as the most prevalent pathogenic yeast species of the Candida-non albicans (CNA) group. Antibiotic affects of Apple Cider Vinegar (ACV) were investigated on the two species C. albicans and C. tropicalis using the disc diffusion method. The effect of four ACV concentrations on the Candida species was determined by measuring the zone of inhibition. A one-way analysis of variance (ANOVA) was carried out for the diameter of inhibition of ACV on the two yeast species. A multiple comparisons for the four concentrations of ACV used and the two controls clotrimazole (positive) and distilled water (negative) were done using Tukey post hoc test. The results revealed that the effect of apple cider vinegar on Candida albicans was significant (p <0.05) and there was a significant differences between the means of both C. albicans and C. tropicalis. This study indicated that Apple cider Vinegar can be effectively used for the treatment of yeast infections associated with Candida albicans and Candida tropicalis.